Common Secondary Causes of Resistant Hypertension and Rational for Treatment. (23rd January 2011) - Faselis, Charles; Doumas, Michael; Papademetriou, Vasilios
Abstract : Resistant hypertension is defined as uncontrolled blood pressure despite the use of three antihypertensive drugs, including a diuretic, in optimal doses. Treatment resistance can be attributed to poor adherence to antihypertensive drugs, excessive salt intake, physician inertia, inappropriate or inadequate medication, and secondary hypertension. Drug-induced hypertension, obstructive sleep apnoea, primary aldosteronism, and chronic kidney disease represent the most common secondary causes of resistant hypertension. Several drugs can induce or exacerbate pre-existing hypertension, with non-steroidal anti-inflammatory drugs being the most common due to their wide use. Obstructive sleep apnoea and primary aldosteronism are frequently encountered in patients with resistant hypertension and require expert management. Hypertension is commonly found in patients with chronic kidney disease and is frequently resistant to treatment, while the management of renovascular hypertension remains controversial. A step-by-step approach of patients with resistant hypertension is proposed at the end of this review paper.